DIGITAL LITERATION: DENING NETWORK-BASED HOAKS LANGUAGE IN THE NEWS A COVID-19 PANDEMIC DISCOURSE IN INDONESIA - Muhsyanur Muhsyanur (XXXXXXXX, 2025)
The development of information and communication technology is increasingly sophisticated. The presence of information and communication technology has brought many impacts, both negative and positive impacts. For those who do not understand the essence and purpose of the presence of information and communication technology, certainly more negative impacts than positive impacts. Especially in the news, many people who are not responsible for using information and communication technology as a means to spread news or events that are troubling and contain elements of untruth, namely news hoaks. In hoaks news, of course it cannot be separated from language games as a medium for broadcasting various information. This research presents opinions on how to counteract the language of news hoaks in the coverage of the Covid-19 pandemic discourse, especially in Indonesia.